Global Database on Nominal Rate of Protection (NRP) 2023 - AgIncentives Consortium (International Food Policy Research Institute, 2023)
This global database on the nominal rate of protection (NRP) in agriculture covers 72 countries and regions (EU treated as one region) from 2005-2021. The NRP measures the extent to which a set of agricultural policies affects the market price of a product relative to prices that would have been in place had there been no interventions. It is computed as the price difference, expressed as a percentage, between the farm gate price received by producers and an undistorted reference price at the farm gate level.